Prevalence and knowledge of hypertension among students of medical college of central Uttar Pradesh, India - Saxena, Saurabh; Rani, Vidya; Srivastava, Dhiraj Kumar; Bajpai, Prashant Kumar; Jain, Pankaj Kumar; Srivastava, Karishma (Indian Journal of Community Health, 2021)
Background: Hypertension is one of the biggest health challenges, which is continuously increasing among young adults, especially students. The aim of the present study was to find out the prevalence, associated factors and knowledge of hypertension among undergraduate students of a medical college of a rural area in central Uttar Pradesh, India. Methodology: A cross-sectional study was conducted in one of the medical college of central Uttar Pradesh, India. Data were collected on socio-demographic and behavioral factors, and anthropometric assessments were carried out using standard equipment and procedures. Results: The present research involved 147 undergraduate medical students with a mean age of 21.9±2.2 years. Knowledge about hypertension was poor, average and good among19.7% (n=29), 76.8% (n=113) and 3.4% (n=5) students, respectively. Mean systolic blood pressure (mean SBP) was 127.07 ± 10.109 mm of Hg with a range 110 to 154mm of Hg, and mean diastolic blood pressure (mean DBP) was 80.5 ± 6.587 mm Hg with a range 68 to 94 mm of Hg. Conclusions: Smoking, alcoholism, non-vegetarian diet, body weight over 60 kgs and waist-hip ratio over 0.9 were recognized as risk factors of hypertension. Hence it needs a powerful surveillance program to find the exact problem.